Promotion for Injecting Drug User utilizing Voluntary Counselling Testing Services among Drug Users: A Study of Pattani Drug Dependence Treatment Center - ไทยเจริญ, นิ่มอนงค์; อาภาคัพภะกุล, นวลตา (Disease Control Journal, 2009)
This qualitative research aimed to: 1) develop a model for early investigation in IDU group, and 2) find the evidence of HIV infection in drug users . The subjects were 49 drug users, and 22 nurses at the Pattani Drug Dependence Treatment Center. The results revealed that among 49 drug users, 9 were injecting drus users practicing needle sharing. Before starting the program, 22 nurses completed a pre-test knowledge about VCT(Voluntary Counselling and Testing), Harm Reduction and Patients' Right, and the average score of VCT was lowest to other categories ( 4.9 from 10, SD 0.78), and also the knowledge in harm reduction average was 5.1 (SD 1.1). The comparison of the knowledge between pre-test and post-test were significantly different (p<0.05). The nurses had to do VCT averaging 2 .3 times (SD 1.2) for each drug users, before they decided to do blood testing for HIV. The prevalence of HIV within the IDU group, we found that they were 100 % HIV positive, and other drug users were 100 % HIV negative. All The nurses thought that the VCT program should be built to the part of the routine screening and care for all drug users. Conclusion: To encourage the VCT among the drug user groups, a very important entry point because The entry point into Voluntary counselling and testing(VCT) is critical, and this program will increase the chances for the group to enter into the ARV (Antiretroviral drugs) program at the Drug Dependency Treatment Center. Early detection of HIV blood test would help either with the appropriate care or advice given to the IDU group.